Fiji - Assessment of the Social Protection System in Fiji and Recommendations for Policy Changes - World Bank (World Bank, 2012)
This summary report is the culmination of a comprehensive, more than a year-long, collaboration between the World Bank, Fiji Department of Social Welfare (DSW), Fiji Islands Bureau of Statistics (FIBOS) and AusAID. It reflects various activities undertaken under the work program that was agreed upon with the Government of Fiji (GOF), with financial support provided by AusAID under the Externally Funded Output (EFO) agreement with the World Bank. The objective of this report is to present the key findings and issues that emerged from the analysis, as well as potential options for policy changes. The recommendations are made with a view of being very concrete, and also with understanding that while some of them could be implemented quickly, others should be considered for medium to long term. This summary report intentionally omits some technical details, since those are available in the accompanying background papers on various issues. The remainder of the report is structured as follows. Section two presents the profile of poverty and vulnerability in Fiji. It is intended to provide a context for the discussion of the social protection system. Section three presents a brief overview of the current social protection system in Fiji. Section four presents the key design features of Family Assistance Program (FAP) and discusses the program's strengths and challenges by looking at the range of the performance indicators. The discussion in this section reflects the findings emerging from the quantitative and qualitative analysis of the FAP. Section five considers some of the policy options for the design of the SP system moving forward. In a way, it provides some 'big picture' ideas and also highlights how much some of the changes could cost from a budget perspective. It also discusses issues related to the development of the new targeting approaches. Section six highlights some of the key findings and recommendations that emerged from the analysis of various operational aspects of the SP system. The activity matrix in the annex presents the suggested work program activities that will need to be implemented in the next couple of years to ensure progress with enhancing the SP system in Fiji.